Melatonin combined with chondroitin sulfate ABC promotes nerve regeneration after root-avulsion brachial plexus injury - Wen-Lai Guo; Zhi-Ping Qi; Li Yu; Tian-Wen Sun; Wen-Rui Qu; Qian-Qian Liu; Zhe Zhu; Rui Li (Neural Regeneration Research, 2019)
After nerve-root avulsion injury of the brachial plexus, oxidative damage, inflammatory reaction, and glial scar formation can affect nerve regeneration and functional recovery. Melatonin (MT) has been shown to have good anti-inflammatory, antioxidant, and neuroprotective effects. Chondroitin sulfate ABC (ChABC) has been shown to metabolize chondroitin sulfate proteoglycans and can reduce colloidal scar formation. However, the effect of any of these drugs alone in the recovery of nerve function after injury is not completely satisfactory. Therefore, this experiment aimed to explore the effect and mechanism of combined application of melatonin and chondroitin sulfate ABC on nerve regeneration and functional recovery after nerve-root avulsion of the brachial plexus. Fifty-two Sprague-Dawley rats were selected and their C5–7 nerve roots were avulsed. Then, the C6 nerve roots were replanted to construct the brachial plexus nerve-root avulsion model. After successful modeling, the injured rats were randomly divided into four groups. The first group (injury) did not receive any drug treatment, but was treated with a pure gel-sponge carrier nerve-root implantation and an ethanol-saline solution via intraperitoneal (i.p.) injection. The second group (melatonin) was treated with melatonin via i.p. injection. The third group (chondroitin sulfate ABC) was treated with chondroitin sulfate ABC through local administration. The fourth group (melatonin + chondroitin sulfate ABC) was treated with melatonin through i.p. injection and chondroitin sulfate ABC through local administration. The upper limb Terzis grooming test was used 2–6 weeks after injury to evaluate motor function. Inflammation and oxidative damage within 24 hours of injury were evaluated by spectrophotometry. Immunofluorescence and neuroelectrophysiology were used to evaluate glial scar, neuronal protection, and nerve regeneration. The results showed that the Terzis grooming-test scores of the three groups that received treatment were better than those of the injury only group. Additionally, these three groups showed lower levels of C5–7 intramedullary peroxidase and malondialdehyde. Further, glial scar tissue in the C6 spinal segment was smaller and the number of motor neurons was greater. The endplate area of the biceps muscle was larger and the structure was clear. The latency of the compound potential of the myocutaneous nerve-biceps muscle was shorter. All these indexes were even greater in the melatonin + chondroitin sulfate ABC group than in the melatonin only or chondroitin sulfate ABC only groups. Thus, the results showed that melatonin combined with chondroitin sulfate ABC can promote nerve regeneration after nerve-root avulsion injury of the brachial plexus, which may be achieved by reducing oxidative damage and inflammatory reaction in the injury area and inhibiting glial scar formation.